Active life–active mind? Associations between active travel and cognitive functions across the lifespan: a systematic review - Melinda Herfet; Anna Timperio; Emiliano Mazzoli; Susanne Tittlbach (Cogent Social Sciences)
Particular types of physical activity (PA) hold the potential to enhance brain structure and functions across various age groups. Active travel (AT), a non-motorised human-powered mode of transportation, might be a particularly important form of PA that may enhance neuropsychological development, benefit executive and visuospatial cognitive abilities, and contribute to preventing cognitive degeneration. Accordingly, this systematic review explores the associations between AT and cognitive outcomes in all age groups. Searches were conducted in five databases. Of 2401 initial hits, 11 studies met the inclusion criteria. The studies ranged from 36 to 2702 participants, examined diverse cognitive outcomes, and were predominantly with children or adolescents. No studies among adult ages 20- to 60-years were included, while only one study among older adults was included in the review. There was some evidence of positive associations between AT and spatial and reasoning abilities. Mixed results were identified between AT and executive functioning and processing speed, and no associations between AT and general intelligence. Limitations included reliance on self-reported AT, a focus mainly on school travel, and heterogeneity of cognition measures. Overall, this review reveals insufficient evidence for an association between AT and cognitive functions across the lifespan, underscoring the need for further investigation.